Pengaruh Kualitas Pelayanan Dan Kepuasan Tamu Terhadap Tingkat Kunjungan Tamu Di Cliff Bar at Six Senses Uluwatu - I Putu Agus Pradnyana; I Wayan Restu Suarmana (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of service quality and guest satisfaction on the level of guest visits at Cliff Bar at Six Senses Uluwatu. This research is motivated by guest complaints regarding service quality and the mismatch between guest expectations and the services received. The research method used is a quantitative approach, with data collected through the distribution of questionnaires to guests. The variables examined in this study include service quality, guest satisfaction, and the level of guest visits. Data analysis was conducted through instrument testing, classical assumption tests, multiple linear regression analysis, coefficient of determination test, as well as F-test and t-test. The results of the study indicate that service quality has a significant effect on guest satisfaction, and guest satisfaction also has a significant effect on the level of guest visits. The conclusion of this study emphasizes that continuous improvement in service quality and guest satisfaction plays an important role in increasing the level of guest visits at Cliff Bar at Six Senses Uluwatu. Keywords: Service Quality, Guest Satisfaction, Guest Visit Level, Hotel